Impact of income generating projects on the rural livelihoods: the case of Mwenezi Fish Conservation Project, Zimbabwe - Mufudza, Pardon (University of Limpopo, 2016)
Most rural communities in developing countries are involved in various natural resource exploitation programmes to improve their livelihood status. The main objectives of the research were to assess the contribution of fish conservation as a strategy towards improving the livelihood status of people in Maranda Ward 9 in Mwenezi, Zimbabwe, and to ascertain the challenges in fish conservation and access to fishing activities. In this research, a questionnaire, interviews, focus group discussions and observations were used to gather information. In the administration of the questionnaires on the village households, 80 households were used as research subjects drawn from a 10% sample size for each of the 10 villages. Purposive sampling was also used for selecting respondents for the interviews and focus group discussions. Secondary data sources used include data from the Parks and Wildlife Authority on recorded cases of fish poaching. The researcher discovered that the fish conservation project improved the livelihood status of the people. Food security was improved through supplementary purchases of food using money derived from the selling of fish. A decrease in school dropouts and improved income are some of the indicators of improved livelihood status of the people. However, there is still a need for continuous support to the programme from various external institutions such as universities, research institutions, financial institutions and Rural District Council. These institutions play a significant role in community development through educational support, training and development, financial support and in creating a favourable environment for economic development in rural areas. There is also a need for continuous monitoring and evaluation of all project activities to assess improvements in rural livelihoods and also compare the actual performance of the IGPs with the desired performance. The deviation makes a platform for corrective actions towards improving the lives of rural people
Thesis (M. Dev.) -- University of Limpopo, 2016
Keywords: Income generating projects; Rural livelihoods; Conservation of natural resource--Zimbabwe; Natural resource